Whole systems approaches to obesity and other complex public health challenges: a systematic review. (13th November 2019) - Bagnall, A; Radley, D; Jones, R; Gately, P; Nobles, J; van Dijk, M; Blackshaw4, J; Montel, S; Sahota, P
Abstract: Background: Increasing awareness of the complexity of public health problems, including obesity, has led to growing interest in whole systems approaches (WSAs). We carried out a systematic review of WSAs targeting obesity and other complex public health and societal issues. Methods: Seven electronic databases were searched from 1995 to 2018. Studies were included if there had been an effort to implement a WSA. Study selection was conducted by one reviewer with a random 20% double checked. Data extraction and validity assessment were undertaken by one reviewer and checked by a second reviewer. Narrative synthesis was undertaken. Results: 65 articles were included; 33 about obesity. Most examined multicomponent community approaches, and there was substantial clinical and methodological heterogeneity. Nevertheless, a range of positive health outcomes were reported, with some evidence of whole systems thinking. Positive effects were seen on health behaviours, body mass index (BMI), parental and community awareness, community capacity building, nutrition and physical activity environments, underage drinking behaviour and health, safety and wellbeing of community members, self-efficacy, smoking and tobacco-related disease outcomes. Features of successful approaches reported in process evaluations included: full engagement of relevant partners and community; time to build relationships, trust and capacity; good governance; embedding within a broader policy context; local evaluation; finance. Conclusions: Systems approaches to tackle obesity can have some benefit, but evidence of how to operationalise a WSA to address public health problems is still in its infancy. Future research should: (a) develop an agreed definition of a WSA in relation to obesity, (b) look across multiple sectors to ensure consistency of language and definition, (c) include detailed descriptions of the approaches, and (d) include process and economic evaluations. Key messages: Interventions working towards systems approaches are associated with a range of positive health outcomes. Evidence of systems science and systems thinking was less clear, even in the most "joined up" approaches.